2009
DOI: 10.3346/jkms.2009.24.6.1177
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Ureaplasma parvum and Ureaplasma urealyticum in Women with Cervical Dysplasia in Katowice, Poland

Abstract: The aim of this study was to evaluate the occurrence of genital mycoplasmas, especially Ureaplasma parvum and Ureaplasma urealyticum, in women with atypical squamous cells of undetermined significance (ASCUS), low grade squamous intraepithelial lesions (LSIL) and high grade squamous intraepithelial lesions (HSIL), compared to women with normal cytology living in Katowice, Poland. Two sterile swabs were used to obtain material from the posterior vaginal fornix of 143 women with squamous intraepithelial lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 19 publications
1
23
0
4
Order By: Relevance
“…Mollicutes have been described for over 30 years as being related to urogenital disorders. Some species are the main cause of non-gonococcal and non-chlamydial urethritis, as in the case of bacterial vaginosis 31. Mollicutes may induce the release of cytokines and chemokines and may cause intense inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Mollicutes have been described for over 30 years as being related to urogenital disorders. Some species are the main cause of non-gonococcal and non-chlamydial urethritis, as in the case of bacterial vaginosis 31. Mollicutes may induce the release of cytokines and chemokines and may cause intense inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Zdorowska-Stefanov et al [16] found slightly lower ureaplasma prevalence (29.8% of 541 women tested), while Kechagia et al [17] found slightly higher prevalence (37.0% of 369 women tested). Molecular based studies have shown that most of ureaplasma isolates thus far considered UU were actually UP [18][19][20]. According to Kacerovský et al [21], the prevalence of UP in a cohort of healthy women who were not pregnant was 57%, which is a much higher prevalence than those of other genital mycoplasmas, viruses, Chlamydia or GBS infections.…”
Section: Discussionmentioning
confidence: 99%
“…MH, UU, 그리고 UP는 비임균성 요도염, 전립선염, 자궁경부염, 자궁내막염, 산후열, 불임, 조기 분만 진통, 조기 양막 파열 등과 관 련이 있다는 보고가 있으나 [1,2,[7][8][9], 건강한 성인 남녀의 비뇨생 식기에도 정상 상재균으로 존재하기 때문에 그 병원성에 대하여는 논란이 있어 왔다 [1,2,7,10]. 따라서 이들 균들은 단순히 균이 검 출되었다는 결과만으로 치료를 시작하지 않고 임상증상을 고려하 여 치료 여부를 선택하게 된다 [11].…”
unclassified